KONSEPSI PENDIDIKAN KARAKTER BERBASIS AL-QUR’AN - Moh Aman (Tadarus Tarbawy Jurnal Kajian Islam dan Pendidikan, 2019)
The success of al-Qur'an based education does not depend on one component only, but it involves all the components that can not be separated from one another, so that the main goal of education can be achieved. From the writing, it can be concluded that character education is a spirit in the conception of al-Qur'an based education that can foster the potential of students to become souls with better values. The existence of character education is even to foster characters that have actually been embedded in every student, so that character education is more to foster, strengthen and maintain so as not to come out of the concept of the Koran so that it can run in line with character education that is actually not apart from the concept of al-Qur'an based education which among others can foster good qualities in each student. The application of the concept of character education in the Qur'an in the context of character education today is by growing values that are carried out every day both in the family and school environment and making it a good habit, so that these values can be used as a basis sturdy and strong in building character.Kata kunci: Pendidikan, Karakter, Al-Qur’an